The Challenges And Marketing Strategy of Indonesia Tire Market Leader Against An Aggressive Competition - Setra Setiadi, Ario (Dinasti Publisher, 2025)
The Indonesian tire industry has experienced speedy advancement, drawing in around the world makers such as Hankook Tire from South Korea. This paper analyzes the competitive scene of Indonesia's tire advertise, centering on the imperative response of PT Multistrada Arah Sarana, Tbk (MASA) to Hankook's showcase segment. The consider highlights the challenges gone up against by MASA in keeping up its grandstand position against a commanding competitor leveraging fetched inclinations, nationalistic branding, and strong around the world organizations. Through an appraisal of MASA's exhibiting strategies—including bargains movement, specialized back, after-sales advantage, and extraordinary activities—the paper proposes crucial recommendations. These joins progressing client associations, optimizing dispersal channels, and exploring co-branding openings with major car makers. The consider help talks almost the moving stream between middle-up and middle-low exhibit parts, emphasizing the require for MASA to reinforce its position within the middle of extended competition. By leveraging its built-up transport organization and brand esteem, MASA can brace its competitive edge whereas altering to industry designs. This examination gives encounters for tire makers looking to investigate creating markets with powerful exterior members and moving buyer slants.